2014
DOI: 10.1016/j.jash.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The impact of hypertension on cerebral perfusion and cortical thickness in older adults

Abstract: Background Hypertension may increase risk for dementia possibly because of its association with decreased cortical thickness. Disturbed cerebral autoregulation is one plausible mechanism by which hypertension impacts the cerebral structure, but the associations among hypertension, brain perfusion, and cortical thickness are poorly understood. Methods The current sample consisted of 58 older adults with varying levels of vascular disease. Diagnostic history of hypertension and antihypertensive medication stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(59 citation statements)
references
References 68 publications
(64 reference statements)
2
55
1
Order By: Relevance
“…Virtanen et al 2003) have also been shown to be associated with negative brain structural (morphological) outcomes (e.g. Alosco et al 2014). Longitudinal studies are necessary to clarify the role of aging in the association of cortical thickness and HRV to address potential (1) top-down (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Virtanen et al 2003) have also been shown to be associated with negative brain structural (morphological) outcomes (e.g. Alosco et al 2014). Longitudinal studies are necessary to clarify the role of aging in the association of cortical thickness and HRV to address potential (1) top-down (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it might be possible that the bidirectional relationship between change in CBF and brain atrophy is not modified by the presence of cardiovascular risk factors although these cardiovascular risk factors could be determinants for reduced CBF and brain atrophy separately. 33,[43][44][45][46] Finally, the possibility of residual confounding because of an unknown confounder cannot be completely ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study in elderly subjects has demonstrated a decreased temporal and occipital brain perfusion, total and regional cortical thickness in participants with hypertension when compared to those without hypertension [44]. The negative impact of hypertension on total brain perfusion remained reduced irrespective of patients’ age.…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of hypertension on total brain perfusion remained reduced irrespective of patients’ age. Reduced total brain perfusion predicted a decrease in cortical thickness whereas antihypertensive therapy was unrelated to total cerebral perfusion or cortical thickness [44]. …”
Section: Introductionmentioning
confidence: 99%